Constraints in Adoption of Laser Land Levelling Technology in Haryana (Indian Journal of Extension Education, 2022)
The study analyzed perceptions of farmers about laser land levelling and constraints faced by them in adoption of this resource conservation technology in Sirsa and Karnal district of Haryana. Mean percent score tool of statistics was used to rank perceptions and constraints of farmers. It was noticed that 97.00 per cent respondent farmers believed that there is reduction in irrigation cost. 80.00 per cent believed that laser land levelling adoption helped in better weed management. Also, it was examined that major constraint was non-availability of machines due to shorter window between two consecutive crops. Study of diffusion revealed that fellow farmers and relatives were major source of diffusion. 86.25 per cent of laser land levelling service provided by private players showing dominance of private investment. It was also observed that laser land levelling is a scale neutral technology because it was adopted by all categories of farmers and not biased towards large farmers. It was observed that under scheme Rashtriya Krishi Vikas Yojana (RKVY) laser leveller along with tractor and operator at a custom hiring centre (CHC) was provided at nominal rate Rs. 1075/day while Cooperatives provided laser leveller at rupees 575 per acre.